Evaluation of the stability of measles vaccine out of the cold chain under extended controlled temperature conditions. Issue 11 (4th March 2020) - Juan-Giner, Aitana; Alsalhani, Alain; Panunzi, Isabella; Lambert, Vincent; Van Herp, Michel; Gairola, Sunil
Abstract: Measles outbreaks occur periodically in remote and difficult to reach areas in countries such as the Democratic Republic of Congo. The possibility to keep measles vaccines at temperatures outside the cold chain for a limited period prior to administration would be an advantage for organizations such as Médecins Sans Frontières, which repeatedly respond to measles outbreaks in difficult contexts. Using stability data at 37 °C and 40 °C provided by Serum Institute of India Private Limited we applied the product release model for Extended Controlled Temperature Conditions (ECTC) to evaluate the possibility of an out of the cold chain excursion. Measles vaccine in the lyophilized form remains above the minimum required potency at the end of the shelf-life for up to 6 days at 37 °C or for 2 days at 40 °C. This evaluation supports the use of a monodose presentation of measles vaccine in ECTC. This could be an advantage for outbreak response in isolated and difficult to reach areas. However the operational advantages of this approach need to be established.